2013
DOI: 10.1371/journal.pone.0080408
|View full text |Cite
|
Sign up to set email alerts
|

A Point Mutation in the Gene for Asparagine-Linked Glycosylation 10B (Alg10b) Causes Nonsyndromic Hearing Impairment in Mice (Mus musculus)

Abstract: The study of mouse hearing impairment mutants has led to the identification of a number of human hearing impairment genes and has greatly furthered our understanding of the physiology of hearing. The novel mouse mutant neurological/sensory 5 (nse5) demonstrates a significantly reduced or absent startle response to sound and is therefore a potential murine model of human hearing impairment. Genetic analysis of 500 intercross progeny localized the mutant locus to a 524 kilobase (kb) interval on mouse chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In the present work, two nonsynonymous (L8S and S28T) amino acid substitutions were determined compared to the native GH protein. L8S may have in uenced the 3D structure of the GH because leucine is relatively and non-polar amino acid, whereas serine is smaller and more polar amino acid (Probst et al, 2013). In literature, some studies have been reported on the replacement of the leucine with serine amino acid which causes a signi cant result, thereby probably signi cant change of the 3D structure of the proteins (Probst et al, 2013;Sürmeli et al, 2019Sürmeli et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, two nonsynonymous (L8S and S28T) amino acid substitutions were determined compared to the native GH protein. L8S may have in uenced the 3D structure of the GH because leucine is relatively and non-polar amino acid, whereas serine is smaller and more polar amino acid (Probst et al, 2013). In literature, some studies have been reported on the replacement of the leucine with serine amino acid which causes a signi cant result, thereby probably signi cant change of the 3D structure of the proteins (Probst et al, 2013;Sürmeli et al, 2019Sürmeli et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
“…L8S may have in uenced the 3D structure of the GH because leucine is relatively and non-polar amino acid, whereas serine is smaller and more polar amino acid (Probst et al, 2013). In literature, some studies have been reported on the replacement of the leucine with serine amino acid which causes a signi cant result, thereby probably signi cant change of the 3D structure of the proteins (Probst et al, 2013;Sürmeli et al, 2019Sürmeli et al, , 2022. Therefore, variation depending on its new function may be eliminated from the population in the next generations.…”
Section: Discussionmentioning
confidence: 99%
“…ALG10 (OMIM: 618355), encoding a membrane-associated protein, might be associated with nonsyndromic hearing impairment in mice. Currently, there is no pathogenic evidence on ALG10 duplication [33].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used an automated threshold detection based on previous publications (Alvarado, Fuentes‐Santamaria, Gabaldon‐Ull, Blanco, & Juiz, ; Bogaerts, Clements, Sullivan, & Oleskevich, ; Probst et al, ). Software "R" (The R Foundation, version 3.2.1, R Core Team 2015) was combined with the additional packages “reshape2” (version 1.4.1), “ggplot2” (version 1.0.1), “data.table” (version 1.9.4), “gdata” (version 2.13.3), “pastecs” (version 1.3.18), “waveslim” (version 1.7.5) and “MassSpecWavelet” (version 1.30.0; Du, Kibbe, & Lin, ) for data processing and analysis.…”
Section: Methodsmentioning
confidence: 99%